Reactive power compensation, system and voltage stability of an industrial network with short circuit limiting coupler - Shikoana, Victor (Department of Electrical Engineering, 2016)
This thesis investigates Sasol Three (Secunda) system's needs for reactive power compensation under voltage and transient stability conditions. A short circuit limiting coupler is designed and the transient and voltage stability studies are performed with a short circuit limiting coupler (SLC) applied at the two 132 kV incoming supply lines from Eskom. The simulations are based 011 solving ordinary loadflow cases augmented with dynamic models of the system elements. Motor loads were modelled in detail incorporating their dynamic characteristics. 75% of the Sasol Three system load constitute induction motors and 25 % is constant impedance and constant current load models. Power System Simulator (PSS/E) package was utilized in carrying out these studies. The most impressive results is the way the Sasol Three System recovers in the range of milliseconds when subjected to severe disturbance with regard to voltage and transient stability. With a short circuit limiting coupler included at the two incoming supply lines, the system still recovers after being subjected to a disturbance. In this project it is shown that there is no need to install reactive power compensation system on the Sasol Three System. This is because of the capabilities of the present system in regulating reactive power through the network during abnormal system conditions. It is also shown in this thesis that the Sasol Three network is transient and voltage stable when a short circuit limiting reactor is applied at the incoming lines from Eskom. The extent to which the-network is transiently stable is also determined.